Cavitech Cavite Provincial Skills Development Center - Ordono, Cathleen H. (College of Architecture, University of the Philippines Diliman, 2019)
Located along Governor's Drive, ont of the main arteries in Cavite, and less than one kilometer away from the Provincial Capital, Cavitech: Cavite Provincial Skills Development Center aims to become the center of community activities in the city, while promoting the culture of technical vocational education and training to the public. The training programs offered by the institute focuses on the two of the key sectors in the economic development of Cavite, the Service and Manufacturing sectors. This development aims to provide quality training for students pursuing higher levels of national certification. By integrating public facilities and community services into the technical-vocational institution, the development creates an environment that will improve the public's opinion on the educational program, raising its reputation in the community and becoming a highly recognized contributor to its economic development through relevance, merging, and transparency.